2002
DOI: 10.1509/jmkr.39.3.366.19104
|View full text |Cite
|
Sign up to set email alerts
|

Can Repeating a Brand Claim Lead to Memory Confusion? The Effects of Claim Similarity and Concurrent Repetition

Abstract: Repetition of brand claims is frequently used to promote the learning of brand-related information. Using dual component models of recognition memory, the author examines whether repetition, in the face of repetitions by similar competitors, might paradoxically increase memory confusion. In Experiment 1, the repetition of similar claims of equally familiar competitor brands produced two opposing effects: It increased memory for accurate claim recognition but also elevated brand claim confusion among advertised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 37 publications
4
22
0
1
Order By: Relevance
“…This result highlights Law's (2002) finding for the need of high binding between memory and brand claims in highly advertised markets.…”
Section: Discussionsupporting
confidence: 64%
“…This result highlights Law's (2002) finding for the need of high binding between memory and brand claims in highly advertised markets.…”
Section: Discussionsupporting
confidence: 64%
“…In fact, Law and Braun (2000) found that implicit memory was dissociated from explicit memory. Implicit memory can be described as enhanced task performance, for example, identifying and processing brand information more easily (Janiszewski & Meyvis, 2001;Law, 2002). Advertising exposure can enhance implicit memory for the brand (and thus affect consumers' responses to the brand at a later encounter) without enhancing explicit memory, such as ad recall (Law & Braun, 2000).…”
Section: Brand Exposure and Ad Recallmentioning
confidence: 99%
“…firm makes the estimation of such a model unreliable. A valuable alternative is offered by the Generalized Estimating Equations (GEE) method 4 (Diggle, Liang, & Zeger, 1994;Law, 2002;Hardin & Hilbe, 2003). This technique is a regression method for correlated data where correlations among observations related to the same firm are estimated and used to re-weight the data when coefficients and standard errors are estimated.…”
Section: Model Estimationmentioning
confidence: 99%